المسيحية في الأدبيات الغربية الحديثة شيفرة دافينشي-أنموذج ا - حشيفة, سناء; سواكر, سعاد (جامعة الوادي university of eloued, 2020)
عالجت هذه الدراسة المعنونة ب: المسيحية في الأدبيات الغربية الحديثة شيفرة دافينشي أنموذجً ا- إشكالية رئيسية حددت في السؤالين الآتيين:كيف هي المسيحية في الأدبيات الغربية الحديثة من خلال شيفرة دافينشي؟ و هل حافظ الأدب الغربي الحديث على العقائد والطقوس المسيحية؟ وللإجابة على الإشكالية اتبعنا خطة من خمس مباحث شرحنا في التمهيدي مصطلحات الدراسة ثم عرفنا بالدين المسيحي، وتطرقنا للعقائد، الشعائر ومصاد ره في التشريع ثم ما أوردته الرواية بشأن ذلك وتوصلنا بذلك إلى جملة من النتائج من أهمها اعتماد الكاتب في نقض ربانية مصادر التشريع المسيحي على اكتشافات علمية )مخطوطات البحر الميت( كما طرحت الرواية جملة من الآراء العقدية المخالفة لما تعارف عليه المسيحيون والكنيسة. وقد كان لهذه الرواية أار بالغة الأهمية وأاارت ضجة كبيرة في مختلف الأوساط. كما أنها كانت دافع لإعادة النظر في الديانة المسيحية. فمن المهم التوجه لمثل هذه الدراسات مع ضرورة الكشف عن المخزون المعرفي بين المدلس والحقيقي في الأدبيات الغربية الحديثة-الرواية تحديدً ا- واستقراء مدى تأايرها في إيمانيات وعقائد المسيحيين. Summary This study, entitled B: Christianity in modern Western literature, addressed the Da Vinci Code as a model - a major problem identified in the following questions: How is Christianity in modern Western literature through the Da Vinci Code? Has modern Western literature preserved Christian doctrines and rituals? In order to answer the problem, we followed a plan of five investigations that we explained in the preliminary terms of the study and then we learned about the Christian religion, and we discussed the doctrines, rituals and sources in the legislation, and then what the novel mentioned about this and we reached a number of results, the most important of which was the adoption of the author in the refutation of the sources of Christian legislation on scientific discoveries (Dead Sea Scrolls) as the novel put forward a number of nodal opinions contrary to what Christians and the Church are familiar with. This novel has had a very important impact and has caused considerable uproar in various quarters. It was also a motivation to reconsider Christianity. It is important to go to such studies with the need to reveal the knowledge stock between the massed and the real in modern Western literature - the novel in particular - and to extrapolate the extent of their influence on the faiths and beliefs of Christians.
ليسانس